Contribution of Graduation Final Projects to vocational Guidance, University of Costa Rica (2012-2023) - Chaves Vargas, Raquel (2025)
This study is a documentary research made in 2024, of the Final Graduation Project (FGP) of the Bachelor's Degree in Educational Sciences with emphasis in Guidance at the University of Costa Rica (2012-2023). The objective is to highlight the contribution made to vocational guidance of the Final Graduation Project. A qualitative approach was used, and the categories of analysis were referenced vocational approaches, theoretical components, research methodology and main findings for the comprehension of vocational guidance. To collect information, the FGP were accessed through the institutional repository OPAC and Kérwá, analyzing a total of 15 relevant documents. These were processed by coding and categorizing data using the ATLAS.ti software, which made it possible to identify the main themes and conclusions in the area. Among the contributions, the conceptualization of Guidance as a professional accompaniment based on processes stands out. In addition, it was concluded that the main reference approaches used are those developed in the last century (traits and factors and career development). The topics investigated included life project, career choice and change, gender issues in choices, and the influence of external factors on choices. Furthermore, the results highlight the importance of age and gender in vocational choices. It was concluded that some less explored themes, which can significantly contribute to vocational guidance are soft skills, work-life balance and validation of vocational exploration instruments.